itu Evaluation of the Suitability of Sustainable Corn Planting Land in Popayato District, Pohuwato Regency - Nusi, Wirdawati; Yulistia Lakoro; Saptan Gobel; Moch. Rio Pambudi; Sunarty Suly Eraku (Tinta Emas Institute, 2023)
Utilization of land resources requires information on the potential and limitations of land use so that the commodities to be cultivated can achieve optimal results. This research aims to determine the suitability of land for corn (Zea mays L.) in Popayato District, Pohuwato Regency. This research uses a qualitative methodology that combines a statistical analysis approach with spatial analysis techniques. Results of pH, texture, effective depth, organic C-C, clay CEC, temperature, rainfall, drainage, slope, height and erosion. Corn plants require an optimal temperature of between 26 °C and rainfall of 807–1200 mm annually, which is a uniform distribution of rainfall. The soil has a clay, dusty loam or sandy loam texture which is ideal for the growth and development of corn. Corn requires sufficient aeration so that the plant roots can absorb nutrients properly. The soil drainage is good and the growth rate is quite fast.